Lo-Tech and Hi-Tech Baby Diaper Machines, Assessment of Performance and Economy - Ahmed, Hasabo A Muhammad; Rajendran, R. (Gezira Journal of Engineering and Applied Sciences, 2018)
The huge consumption of baby diapers worldwide (81, 993, 30) millions has derived many investors to enter as converters. The market of baby diapers is a very competitive market. Consequently, to capture a market niche one has to decrease the diaper cost effectively. The cost variables are raw material, machine depreciation, manpower, energy, and infrastructure. To reduce the cost of any product one should look into the component that represents the highest percentage of the product cost. In that case the raw material factor should be optimized since it represents 80% of the diaper cost. The performance of machine in terms of quality and waste minimization has also been considered. The waste percentage affects the diaper cost dramatically since as the cost of wasted material is high. In this sense the machines that can save on raw material would be the one that can compete well in the baby diaper market war. The raw material cost reduction is normally on waste and carrier tissue paper which is used by Lo-tech machines in lack of vacuum pressure for holding down the diaper during processing. The engineering features of the baby diaper machines are examined in terms of performance and product quality.  In this research a comparative study is conducted to find out the best alternatives to enhance the quality of the baby diaper and increase savings on raw material cost. It is found that the Hi-Tech machine comparatively is the best in terms of performance, least cost, and quality. Consequently, it is the best investment alternative.